Targeted delivery of the PKMYT1 inhibitor RP-6306 mediates PANoptosis in pancreatic cancer via mitotic catastrophe - Jingyun Chen; Jianghao Ren; Chaolei Zhang; Yang Lv; Jingbin Zhou; Weiliang Jiang; Chaojie Huang; Liping Cao (Cell Death and Disease)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant tumor often diagnosed in advanced stages due to its subtle early symptoms, making surgical options nonviable and requiring systemic chemotherapy. Current treatments mainly utilize gemcitabine, which provides limited efficacy. PKMYT1, a serine/threonine protein kinase crucial for cell cycle regulation, is overexpressed in PDAC and correlates with poor prognosis. Treatment with the PKMYT1 inhibitor RP-6306 promotes rapid mitotic entry, resulting in DNA damage and mitotic catastrophe, thereby inducing PANoptosis. RP-6306 effectively inhibits PDAC growth in vitro and in vivo, and shows enhanced anti-tumor activity when combined with gemcitabine, also reducing metastasis. However, gemcitabine has notable systemic toxicity. To target cancer cells more specifically, we utilized vesicles derived from cell membranes (BxPC-3M) to deliver a combination of RP-6306 and gemcitabine (GEM + RP-6306@BxPC-3M). This formulation effectively targets homotypic tumor cells and significantly inhibits tumor growth both in vitro and in vivo. These findings highlight the role of RP-6306 in inducing PANoptosis, characterize PANoptosis as a novel form of cell death associated with mitotic catastrophe, and confirm the synergistic antitumor activity of RP-6306 and gemcitabine in PDAC. Moreover, GEM + RP-6306@BxPC-3M exhibits improved safety and enhanced antitumor efficacy.